The Effect of Science Teaching Based on POE Strategy on the Academic Achievement and Attitudes of Fifth-Grade Students in the Distance Education Process - Sevgül Çalış; Mustafa Özkan (Mimbar Sekolah Dasar, 2022)
The aim of this study is to examine the effect of science teaching based on POE (Predict-Observe-Explain) technique on the academic achievement and attitudes of fifth-grade students in the distance education process. The study was carried out with the quasi-experimental design of quantitative research methods and an approach in which pretest and posttest applications were applied to the experimental and control groups. The research sample consists of 72 fifth grade students, 36 of whom are in the experimental group and 36 in the control group. Data collection tools included an academic achievement test and an attitude scale regarding learning science. The collected data were analyzed with the SPSS package program. The research results concluded that science teaching based on online POE technique increased the students’ academic achievement. Meanwhile, the attitude towards science learning was independent from teaching based on POE strategy.